Enhancing Preschooler's Gross Motoric Using Pocket Book-Flipbook Maker Based - Wulan Patria Saroinsong; Intan Kurnianingtyas; Nurhenti Dorlina; Eka Cahya Maulidiyah (LPPM Universitas Pahlawan Tuanku Tambusai, 2022)
The urgency of study was overcome the lack of gross motor skill in young learners especially during pandemic Covid-19 which is entile online. This study emphasized to elaborate the development, feasibility and effectiveness of the flipbook maker-based concern on children’s gross motor conducted to Indonesian traditional games. This study was conducted to research and development through ASSURE model. The target participant was involved the parents of children in 5-6 years old in Surabaya through online survey instruction to fill the google form regarding their children’s gross motoric development since using the pocket book- flipbook maker. Eventually, this study revealed that the the pocket book- flipbook maker had effective than conventional media (Worksheet) to stimulate the children’s gross motor skills. Furthermore, this study is expected to be able to contribute in early childhood education and technology in particular to enhancing children’s gross motor skills during pandemic Covid-19.